2021
DOI: 10.3390/ph14060505
|View full text |Cite
|
Sign up to set email alerts
|

Action of Carvacrol on Parascaris sp. and Antagonistic Effect on Nicotinic Acetylcholine Receptors

Abstract: Parascaris sp. is the only ascarid parasitic nematode in equids and one of the most threatening infectious organisms in horses. Only a limited number of compounds are available for treatment of horse helminthiasis, and Parascaris sp. worms have developed resistance to the three major anthelmintic families. In order to overcome the appearance of resistance, there is an urgent need for new therapeutic strategies. The active ingredients of herbal essential oils are potentially effective antiparasitic drugs. Carva… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…Briefly, defolliculated Xenopus laevis oocytes (Ecocyte Bioscience) were micro-injected with 36 nL of Asu-ACR-16 cRNA at 50 ng/μL using the Nanoject II microinjector (Drummond). Two micro-electrode voltage-clamp experiments were performed 3 days after micro-injections as previously described ( Trailović et al, 2021 ). Data were collected and analyzed using the pCLAMP 10.4 package (Molecular Devices).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Briefly, defolliculated Xenopus laevis oocytes (Ecocyte Bioscience) were micro-injected with 36 nL of Asu-ACR-16 cRNA at 50 ng/μL using the Nanoject II microinjector (Drummond). Two micro-electrode voltage-clamp experiments were performed 3 days after micro-injections as previously described ( Trailović et al, 2021 ). Data were collected and analyzed using the pCLAMP 10.4 package (Molecular Devices).…”
Section: Methodsmentioning
confidence: 99%
“…In the previous research, we have shown that monoterpenoid carvacrol acts on the neuromuscular system of nematodes and exhibits an inhibitory effect on contractions caused by acetylcholine (ACh) ( Trailović et al, 2015 ). In our following study, carvacrol dominantly exhibited characteristics of a non-competitive antagonist of nicotinic acetylcholine receptor (nAChR) in Ascaris suum ( A. suum ), and enhances the inhibitory effect of monepantel ( Marjanović et al, 2021 ; Trailovic et al, 2021 ).…”
Section: Introductionmentioning
confidence: 92%
“…In addition, some in vivo studies have been carried out on sheep (Štrbac et al 2022). In horses, carvacrol has been studied as the main component derived from EOs of plants for the control of Parascaris (Trailovic et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…In severe cases, the infection with P. equorum is associated with unthriftiness, respiratory signs, or intestinal impaction. In some cases, ascarids can lead to an obstruction and rupture of the small intestine or the death of foals [ 1 , 2 ]. Infection can be diagnosed by detecting eggs in feces, but this is only possible after the worms are fully mature [ 3 ].…”
Section: Introductionmentioning
confidence: 99%